Breastfeeding practice among Malays in community - Jamil, Nurul Akma; Muda, Siti Mariam; Ismail, Hamizah (IIUM Press, 2017)
This book reports a study involving Malay mothers who have had an ongoing breastfeeding experience. The motivation of this book was derived from two main considerations. First, it was driven by the need to explore the influences of religious affiliation experience on breastfeeding practices. Second, mothers’ perception and experience throughout their breastfeeding journey need to be understood in establishing health promotion and education within communities with different context of culture. Our attention on breastfeeding issues is rooted from our life experience as a mother who breastfeeds. The exposures as a health care providers working in Obstetrics Ward allowed us to observe the discrepancy between the religious recommendation and sociocultural perspective within the breastfeeding promotion and education program within the society.